2007
DOI: 10.1002/app.25616
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nonconjugated polymers on the conjugation length and structure of poly(3‐octylthiophene) in ternary polymer blend

Abstract: The shifting of l max (p-p* transition) of P3OT (poly(3-n-octylthiophene)) was used to monitor the degree of miscibility between P3OT and the matrix polymers. In the ternary blend system, 1% of P3OT is soluble in a uniform PMMA/EVA20 mixed matrix and does not interfere with the miscibility between PMMA and EVA20 (ethylene-vinyl acetate copolymer with 20% of vinyl acetate). But 5% of P3OT can attract EVA20 out of the matrix and induce the separation from 95% of PMMA/EVA20 matrix and cause the doublet peak of l … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…The conjugational length of the polymer can be altered by the interaction with matrix polymers resulting in a shifting of k max (change of the conjugation length), the so-called solvatochromic effect. 27,28 In other words, one can perceive the degree of miscibility of a conjugated polymer with other nonconjugated polymers merely from the shifting of its k max or not. Commonly, the presence of miscibility always contributes to a blue shift of k max because of the interruption on the conjugation (flipping of the thiophene rings out of conjugated plane resulting in the reduction of coplanarity) as observed for the p-p* transition of PCDTBT.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…The conjugational length of the polymer can be altered by the interaction with matrix polymers resulting in a shifting of k max (change of the conjugation length), the so-called solvatochromic effect. 27,28 In other words, one can perceive the degree of miscibility of a conjugated polymer with other nonconjugated polymers merely from the shifting of its k max or not. Commonly, the presence of miscibility always contributes to a blue shift of k max because of the interruption on the conjugation (flipping of the thiophene rings out of conjugated plane resulting in the reduction of coplanarity) as observed for the p-p* transition of PCDTBT.…”
Section: Resultsmentioning
confidence: 98%
“…The location of the λ max depends on the length of the conjugation, longer conjugational length resulting in lower p‐p* energy gap ( E g = hν = hc / λ max ) and higher λ max . The conjugational length of the polymer can be altered by the interaction with matrix polymers resulting in a shifting of λ max (change of the conjugation length), the so‐called solvatochromic effect . In other words, one can perceive the degree of miscibility of a conjugated polymer with other nonconjugated polymers merely from the shifting of its λ max or not.…”
Section: Resultsmentioning
confidence: 99%
“…[22][23][24] However, crystallinity can be found if aniline is replaced by ptoluidine, for which only ortho-ortho polymerization is possible. The WAXD patterns of PTF resins of different monomer ratios are shown in Figure 3.…”
Section: Waxd Patternsmentioning
confidence: 98%
“…There are some research works that investigated the miscibility, electromagnetic interference shielding effectiveness, and the phase diagram of P3OT–polystryrene blend 5,2124 or P3OT PVC blend. 5,21 However, to the best of our knowledge, no study has been found to investigate the physical properties of P3OT–PC polymer blend.…”
Section: Introductionmentioning
confidence: 99%